El nivel de la conciencia ambiental en los estudiantes del cuarto grado de secundaria de la Institución Educativa Secundaria Mariscal Oscar Raymundo Benavides, Iquitos 2021 - Andrade Malafaya, Vivian Hilary (2023)
The general objective of this research was to evaluate and identify the level of environmental awareness in fourth grade secondary school students of the Mariscal Oscar Raymundo Benavides Secondary Educational Institution, Iquitos-2021. The study is of a quantitative-descriptive type with a field study, non-experimental and bivariate descriptive transactional design. The population consisted of 436 students and a stratified sample with a proportional fixation of 205 students. The main data collection tool was the survey through a valid and reliable questionnaire using the virtual tools of Google Drive in times of COVID19. The results show empirical evidence at a confidence level of 95%, which shows that the 4 dimensions, affective, cognitive, conative and active, of environmental awareness are average in fourth grade secondary school students of the Mariscal Oscar Raymundo Secondary Educational Institution. Benavides Iquitos-2021. Which determined the importance of environmental education to achieve improvements in the educational and social system that allow us to take care of our environment.